Outside-in perspectives on the socio-econo-technological effects of climate change in Africa - Faiyetole, Ayodele Adekunle (International Sociology)
Humans$1 (Baspirations for development have unsustainably placed momentous pressure on the Earth. Peripheral Africa remains the most susceptible region to climate change and its impacts. By considering externality and world-systems theories, this article uses the Delphi external experts (DEE) approach to weigh the perceptions of global (and mostly core) experts regarding climate change response/sustainability. The socio-econo-technological development factors that contribute to Africa$1 (Bs climate change issues are evaluated. The article concludes that despite the high rankings of the factors related to emissions$1 (Bpropensity, such as energy and transportation, governance and socio-cultural preferences are the two factors that are statistically significant to climate change and vulnerability to it. The global governance structure fostered by the core countries facilitates unequal exchanges. Notwithstanding, responsive governance structures are advised for the periphery. Governance is analogous to a thermostat that can be used to regulate other development factors, in particular to entrench socio-cultural preferences that may have a desirable future impact on the climate. - Reproduced.s